Evaluation of neural networks and fuzzy logic techniques applied to the control of electric machines - Fonseca, Jaime C. (1996)
This paper reports the work that is being developed in the evaluation of neural networks and fuzzy logic techniques applied to the control of electrical machines. An overview of a CACSD (Computer Aided Control System Design) tool – Matlab/Simulink is also presented. This tool was used to design and simulate a control system for an induction motor based on the referred techniques.